2022
DOI: 10.1213/ane.0000000000005990
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Subparaneural Upper Trunk and Conventional Interscalene Blocks for Arthroscopic Shoulder Surgery: A Randomized Noninferiority Trial

Abstract: BACKGROUND: Although interscalene nerve block is the standard for shoulder analgesia, the risk of hemidiaphragmatic paralysis restricts its use in patients with compromised pulmonary function. We hypothesized that a novel subparaneural upper trunk block would provide noninferior postoperative analgesia but superior diaphragmatic sparing effect compared to interscalene block. METHODS: This randomized controlled trial comprised 96 patients who underwent arthroscopic shoulder surgery under either subparaneural up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…The only study of the subparaneural approach's efficacy in clinical practice [ 19 ] corroborated the findings of a prior cadaveric study of this technique [ 52 ]. A possible explanation for this is that the paraneural sheath limits the spread of LA, preventing it from reaching the PN and forcing it to spread within the sheath cranially to the C5/6 nerve roots and SSN and caudally to the lateral pectoral nerve.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The only study of the subparaneural approach's efficacy in clinical practice [ 19 ] corroborated the findings of a prior cadaveric study of this technique [ 52 ]. A possible explanation for this is that the paraneural sheath limits the spread of LA, preventing it from reaching the PN and forcing it to spread within the sheath cranially to the C5/6 nerve roots and SSN and caudally to the lateral pectoral nerve.…”
Section: Discussionsupporting
confidence: 60%
“…A recent study by Zhang et al [ 19 ] has been the only one to investigate the subparaneural approach's efficacy in clinical practice, showing HDP incidences of 16.7% when using 5 mL of LA.…”
Section: Resultsmentioning
confidence: 99%
“…However, the data for the worst resting pain score within 30 min in the recovery room showed a skewed distribution; therefore, the Hodges-Lehmann method was used to assess the difference in pain scores between groups, which showed a median difference of 0 (95% CI −0 to 0). The CI of the effect size is −0 to 0, which is difficult for the reader to understand when drawn on a diagram; thus, in a way similar to our previous study,4 we showed the result in text without drawing a diagram.…”
supporting
confidence: 76%
“…Previous studies examining respiratory complications after interscalene nerve blocks in shoulder surgery patients have either been limited in scope with small sample sizes and short time frame for follow-up (eg, up to 24 hours only), or focused on diagnostic tests (eg, ultrasound of the diaphragm, pulmonary function tests) rather than clinical respiratory complications and subsequent healthcare interventions 3 17 18. For example, Pere studied the effect of CISB with 0.125% bupivacaine with and without fentanyl on diaphragmatic motility and respiratory function in shoulder surgery patients 17.…”
Section: Discussionmentioning
confidence: 99%